Penggunaan Metode Lingkungan Alam Untuk Meningkatkan Keterampilan Menulis Puisi Kelas IV SD Miftahul Ulum Tlogobedah Menganti Gresik - Aulia Silvi Muhasanah; Ainul Fithriyah; Nurul Agustin (InsightEd, 2025)
This study aims to improve the poetry writing skills of fourth-grade students at SD Miftahul Ulum Tlogobedah Menganti Gresik through the implementation of the Natural Environment Approach (PLAS). The research was motivated by the low poetry writing skills of students due to limited real-life experiences and the predominance of monotonous lecture methods. This research employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart model, conducted in two cycles with 22 student participants. Data were collected through observation, tests, documentation, and field notes, and analyzed using descriptive qualitative and quantitative methods. The results showed a significant improvement in students’ poetry writing skills, from an average score of 2.77 (69.88%) with a mastery level of 13.64% in Cycle I to an average score of 3.51 (87.78%) with a mastery level of 100% in Cycle II. All assessment indicators—diction, figures of speech and style, creativity and coherence, and theme suitability—improved, with the greatest increase observed in creativity and coherence (from 50% to 89.77%). Thus, the PLAS method is proven to be effective in enhancing poetry writing skills through contextual, meaningful, and engaging learning.